Prevalence of Polycystic Ovary Syndrome in Fourth Year Medical Students of University of Tripoli - Hayat Abdalla; Nasreen Osman; Amel Morgham; Mohamed Sultan (AlQalam Journal of Medical and Applied Sciences, 2021)
Background and objective. Polycystic ovarian syndrome (PCOS) is considered one of the most common endocrine disorders among women of reproductive age. PCOS is the most prevalent endocrine disorder worldwide that affects 6%–8% of women. It is characterized by enlarged ovaries, chronic anovulation, irregular menstrual cycles, androgen excess, obesity associated with insulin resistance, hirsutism, and infertility. This study aims to find out its prevalence among the female medical undergraduates’ students. Methods. A descriptive cross-sectional study was conducted among 258 females from 4th year medical school, Faculty of Medicine, University of Tripoli from 2013-2014. Results. Cohort age ranged between 22 – 29 years (mean age 23.8±1.3). We found that 27.9% are overweight (BMI between 25-29), 6.2% are obese (BMI >29), and 3% are underweight (BMI < 18). Only 1.6% had menstrual irregularity and 7.8% has signs of hyperandrogenism (hirsutism and/or acne). The prevalence of polycystic ovarian syndrome was found to be (8.1%). Conclusions. the prevalence of polycystic ovarian syndrome in our cohort and was found to be similar to other studies conducted in similar settings. As the PCO is associated with endocrine disorders among women, early screening strategy is necessary to prevent lifelong complications.